Neuromarketing: a systematic review (Research, Society and Development, 2022)
The aim of this systematic review is to elucidate how the Neuromarketing field has been studied in terms of consumer behavior through experimental protocols that make use of statistics (quantitative analysis). At the same time, it aims to verify how new Neuromarketing protocols can better clarify consumer behavior patterns, as well as understand the decision-making process and how to meet consumer needs. Articles dated between 2016 and 2020 were initially collected in the PubMed, Science Direct and DOAJ databases and subjected to a filtering to remove duplicates and apply the exclusion criteria, which resulted in 13 final articles selected. Although studies suggest it is necessary to customize ads, generate positive emotions, use the image and speech of famous people and attractive packaging to be able to capture the consumer's attention, a methodological standardization is necessary among neuromarketing research so that they can be replicated and their hypotheses become capable of being validated.